Analysis of BPJS Based National Health Insurance Program Financing For Sectio Caesarea Birth In Indonesia - Yulidar Ewi; Siska Hermawati; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2025)
The study focused on the purpose of finding out about caesarean section delivery is the last alternative to save the mother and fetus when normal delivery is not possible. The increase in caesarean sections worldwide has become a major public health problem, so there needs to be supervision to reduce the number of caesarean sections that are considered unnecessary, one of which is through the classification. The existence of health insurance for the Indonesian people, including BPJS which covers the cost of caesarean operations, allows for an increase in the incidence of caesarean sections. The purpose of the study was to analyze the financing status of the BPJS based National Health Insurance (JKN) program for caesarean section deliveries. This study used quantitative research with a cross sectional, the research sample was mothers who gave birth by caesarean section who used the BPJS National Health Insurance (JKN). This study discusses reporting for one year in 2023, participants who used BPJS national health insurance for caesarean section deliveries were 1117 participants. With the income of BPJS caesarean section services with hospital rates in UHC (Universal Health Care) 2019, will be implemented, while BPJS health according to Indonesia Law number 24 of 2011 is appointed by the government as a health insurance management agency. Data results show that the incidence of caesarean section using National Health Insurance (JKN) is still very high in hospitals. The management of hospitals needs to calculate service costs using unit costs so as not to experience a deficit and anticipate future management.